Dirāsah Tahlīliyah Limanhaj Tadrīs Mahārat Alqirā'at Fī Kitāb Ta’lim Allughah Al’arabiyah Lilshafi Altsānī Min Almarhalat Almutawasitah Liwizārah Alsyu`ūwn Aldīniyah Al Indūnīsiyah ām 2020 - Ikbal Hidayatullah; Abdurrahim (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2022)
This study aims to know the method used to teach the skill of reading in the textbook of teaching Arabic for the second grade of the intermediate stage of the Indonesian Ministry of Religious Affairs in 2020, and to analyze this curriculum comprehensively to find out the extent to which it fits, its advantages and disadvantages in order to contribute to the teaching of the Arabic language. This study is based on the analytical description method, by reviewing the textbook on teaching Arabic for the second grade of the middle stage of the Indonesian Ministry of Religious Affairs in 2020 and presenting the curriculum for teaching the skill of reading in it, analyzing it, and concluding. As a result of this Research that the methodology of teaching reading skill in a book Teaching the Arabic language for the second grade of the middle school of the Indonesian Ministry of Religious Affairs in 2020 is good and suitable for students at this level, so this textbook is suitable for the development of the Arabic language And that the analysis of the method for teaching the skill of reading in the book teaching Arabic language for the second grade of the middle school of the Indonesian Ministry of Religious Affairs in the year 2020 is in four components: objectives, content, teaching methods, and exercises. Penelitian ini bertujuan untuk mengetahui metode yang digunakan untuk mengajarkan keterampilan membaca dalam buku teks pembelajaran bahasa Arab kelas II Tingkat Menengah Kementerian Agama Republik Indonesia Tahun 2020, dan menganalisis kurikulum tersebut secara komprehensif untuk mengetahui sejauh mana yang cocok, kelebihan dan kekurangannya untuk berkontribusi pada pengajaran bahasa Arab. Penelitian ini didasarkan pada metode deskriptif analitik, dengan mereview buku ajar pengajaran bahasa Arab kelas II tingkat menengah Kementerian Agama Republik Indonesia Tahun 2020 dan menyajikan kurikulum pengajaran keterampilan membaca di dalamnya, menganalisisnya, dan menyimpulkan. Sebagai akibatnya Penelitian itu menggunakan metode pengajaran keterampilan membaca dalam buku Pengajaran Bahasa Arab untuk kelas II Sekolah Menengah Pertama Kementerian Agama RI tahun 2020 sudah baik dan cocok untuk siswa pada jenjang ini, sehingga buku ajar ini cocok untuk pengembangan bahasa Arab . Dan bahwa analisis metode pembelajaran keterampilan membaca dalam buku pengajaran bahasa Arab kelas II SMP Kementerian Agama Republik Indonesia Tahun 2020 ada dalam empat komponen: tujuan, isi, metode pembelajaran, dan latihan. تهدف هذه الدراسة إلى معرفة المنهج المستخدم لتدريس مهارة القراءة في كتاب تعليم اللغة العربية للصف الثاني من المرحلة المتوسطة لوزارة الشؤون الدينية الإندونيسية عام 2020، وتحليل هذا المنهج تحليلاً شاملاً لمعرفة مدى التي تناسبه ومميزاته وعيوبه من أجل إسهام في تعليم اللغة العربية. وتعتمد هذه الدراسة على منهج الوصف التحليلي، وذلك بالاطلاع على كتاب تعليم اللغة العربية للصف الثاني من المرحلة المتوسطة لوزارة الشؤون الدينية الإندونيسية عام 2020 وعرض منهج تدريس مهارة القراءة فيه، وتحليله، والاستنتاج. ونتيجة هذا البحث أن منهج تدريس مهارة القراءة في كتاب تعليم اللغة العربية للصف الثاني من المرحلة المتوسطة لوزارة الشؤون الدينية الإندونيسية عام 2020 جيد ومناسب مع الدارسين في هذا المستوى، لذا هذا الكتاب الدراسي مناسب لتنمية اللغة العربية. وأن تحليل منهج تدريس مهارة القراءة في كتاب تعليم اللغة العربية للصف الثاني من المرحلة المتوسطة لوزارة الشؤون الدينية الإندونيسية سنة 2020 يكون في أربعة عناصر: الأهداف، والمحتوى، وطرق التدريس، والتدريبات